1999
DOI: 10.1021/jm990086a
|View full text |Cite
|
Sign up to set email alerts
|

Enantiospecific Synthesis of 3-Fluoromethyl-, 3-Hydroxymethyl-, and 3-Chloromethyl-1,2,3,4-tetrahydroisoquinolines as Selective Inhibitors of Phenylethanolamine N-Methyltransferase versus the α2-Adrenoceptor

Abstract: An enantiospecific method was developed for the synthesis of 3-fluoromethyl-, 3-hydroxymethyl-, and 3-chloromethyl-7-substituted-1,2,3,4-tetrahydroisoquinolines (THIQs) from phenylalanine. Biochemical evaluation of the enantiomers of these compounds at both PNMT and the alpha(2)-adrenoceptor indicates that both sites display similar stereoselectivity. Overall the R-enantiomer was usually the more potent enantiomer at both PNMT and the alpha(2)-adrenoceptor for these 3-fluoromethyl-, 3-hydroxymethyl-, and 3-chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 33 publications
(84 reference statements)
2
26
0
Order By: Relevance
“…The docking of inhibitors into the hPNMT active site was performed on the R-enantiomer as a previous study on 3-substituted-THIQs indicated that the R-enantiomer is preferred over the S-enantiomer in the hPNMT active site. 60 Difluoroacetonitrile (29) was prepared according to a procedure reported by Swarts. 31 Difluoroacetamide (28, 2.30g, 24.2 mmol) and P 2 O 5 (5.00 g, 17.6 mmol) were stirred to a homogeneous mixture in a 50 mL RB flask equipped with a short path distillation head.…”
Section: Molecular Modelingmentioning
confidence: 99%
“…The docking of inhibitors into the hPNMT active site was performed on the R-enantiomer as a previous study on 3-substituted-THIQs indicated that the R-enantiomer is preferred over the S-enantiomer in the hPNMT active site. 60 Difluoroacetonitrile (29) was prepared according to a procedure reported by Swarts. 31 Difluoroacetamide (28, 2.30g, 24.2 mmol) and P 2 O 5 (5.00 g, 17.6 mmol) were stirred to a homogeneous mixture in a 50 mL RB flask equipped with a short path distillation head.…”
Section: Molecular Modelingmentioning
confidence: 99%
“…2 The addition of small substituents (e.g., methyl, 10) to the 3-position of THIQ increases potency at hPNMT while decreasing affinity for the α 2 -adrenoceptor. 3,4 The absolute stereochemistry at the 3-position of THIQs is important and is discussed below. A synergistic effect is achieved by adding both 3-and 7-substituents to THIQ, resulting in multiplicative increases in PNMT inhibitory potency and selectivity versus the α 2 -adrenoceptor compared to the similarly substituted 3-or 7-monosubstituted THIQs.…”
Section: Introductionmentioning
confidence: 99%
“…15 The docking of inhibitors into the hPNMT active site was performed on the R-enantiomer as a previous study on 3-hydroxymethyl-7-substituted-THIQs indicated that the R-enantiomer is preferred over the S-in the hPNMT active site. 32 Residues Lys57 and Met258 move within the PNMT active site depending on the hydrophobicity of the 7-substitutent. 15 Inhibitors that contain a 7-nitro substituent were docked into the crystal structure of hPNMT co-crystallized with SK&F 29661 (4), 16 whereas inhibitors that possess a 7-bromo substituent were docked into the crystal structure of hPNMT cocrystallized with 7-iodo-THIQ (3).…”
Section: Resultsmentioning
confidence: 99%